Bulk Alignment of Chromonic Aggregates During Swelling of Hydrogels. Issue 10 (4th March 2020) - Shiraishi, Koji; Takahashi, Sawako; Le, Khoa V.; Naka, Yumiko; Sasaki, Takeo
Abstract: This study demonstrates that the bulk alignment of chromonic aggregates can be achieved during the swelling of hydrogels. Swelling of an ionic hydrogel immersed in an aqueous solution of disodium cromoglycate reorients the chromonic aggregates, and millimeter‐thick optically anisotropic hydrogels are obtained. These anisotropic hydrogels contain the chromonic aggregates at a condensed concentration as high as in the columnar phase of a normal chromonic aqueous solution, although the X‐ray diffraction results show much less stacking order and orientational order of the aggregates. Furthermore, anisotropic mechanical properties of the hydrogels are observed due to the anisotropic alignment of the chromonic aggregates. Abstract : Disodium cromoglycate chromonic aggregates are incorporated in a positively charged hydrogel through ionic bonds. They are uniaxially aligned during the swelling of the hydrogel. Such chromonic‐aggregates‐incorporated hydrogels are optically anisotropic and show anisotropic mechanical properties during stretching.